(untitled) (Journal of the College of Basic Education, 2026)
The current study aims to evaluate the performance of geography teachers in preparatory schools in light of job satisfaction criteria, within preparatory and secondary day schools affiliated with the Directorate of the research sample was selected randomly and consisted of 80 teachers, 32 male teachers and 48 female teachers. The current research relied on the descriptive approach as an appropriate method for achieving the research objectives. For this purpose, the researcher prepared a job satisfaction scale (five alternatives) as an appropriate tool for data collection. The scale included four areas or sub-criteria, namely: The job design criterion, which included 12 secondary criteria; the salary system criterion, which included 12 secondary criteria; the administrative system criterion, which included 13 secondary criteria; and the teacher’s interpersonal relationships criterion, which included 13 secondary criteria. The researcher verified the validity and reliability of the scale and used appropriate statistical methods to arrive at the following results: There was a difference in opinion regarding the acceptance, weakness, or neutrality of some sub-criteria for both genders. There were also statistically significant differences between the affirmations of the importance of some of the criteria included in the questionnaire in favor of female teachers. In light of the results, the researcher made a number of recommendations, including using the above list of criteria in the process of evaluating geography teachers in preparatory and secondary schools, and using the above list of criteria in the process of evaluating (students/teachers) in preparatory schools.